Etrog Citron (Citrus medica) as a Novel Source of Antimicrobial Agents: Overview of Its Bioactive Phytochemicals and Delivery Approaches - Arik Dahan; Ludmila Yarmolinsky; Faina Nakonechny; Olga Semenova; Boris Khalfin; Shimon Ben-Shabat (Pharmaceutics)
The rising prevalence of bacterial antibiotic resistance remains a significant challenge, while many existing antibacterial agents exhibit limited efficacy and notable adverse effects. Edible plants offer a promising avenue for developing novel antimicrobial drugs and preservatives. Etrog citron (Citrus medica L.) and its bioactive phytochemicals have demonstrated activity against various pathogenic microorganisms. However, the potential application of these compounds is hindered by factors such as poor solubility, limited bioavailability, and unclear mechanisms of action. This review consolidates key findings on the antimicrobial properties of extracts and essential oils derived from different parts of Citrus medica, emphasizing strategies for improving the delivery of these bioactive compounds.